Noise Reduction Using Synthetic Microjet Excitation in Supersonic Rectangular Jets - Michael Marques; Surabhi Singh; Anastasios Lyrintzis; Vladimir Golubev (Applied Sciences)
This work explores a potential methodology for rectangular jet noise reduction that employs nozzle unsteady microjet excitation. Using high-fidelity computational studies and spectral analyses, major jet noise sources impacted by the applied actuation are identified. A heated supersonic rectangular jet is considered with a nozzle aspect ratio of 2:1 at a Mach number of 1.5. The current study essentially validates the hypothesis of a previous reduced-order analysis that predicted jet noise reduction through jet excitation at the harmonic or subharmonic of the dominant frequency associated with jets’ large-scale structures. Such noise reduction was attributed to the excitation-induced nonlinear energy exchange between the coherent modes. In the current study, the synthetic microjet actuation of the jet plume shear layer using <semantics>1%</semantics> of the jet mass flow rate is implemented at the excitation ports located at the nozzle lip and directed along the jet axis. A resulting jet noise reduction of up to 4 dB at the peak radiation angle is predicted. An analysis of the near-field Spectral Proper Orthogonal Decomposition (SPOD) results provides further insights into the impact of jet actuation on the modification of jet flow structures, thus addressing the effectiveness of the proposed noise control methodology.